Uji Antagonistik Beberapa Rizobakteri terhadap Sclerotium rolfsii Sacc. Penyebab Penyakit Rebah Kecambah pada Tanaman Kacang Tanah - KUNTALINI, NYOMAN RAI; KALIMI, KHAMDAN; PUSPAWATI, NI MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2015)
ABSTRACT Antagonistic Test of Some Rhizobacteria Against Sclerotium rolfsii Sacc . Causes Damping Off Disease in Peanut Plant Damping-off disease is one of the important diseases on peanut plants caused by the fungi Sclerotium rolfsii Sacc . Control which is currently only with synthetic pesticides , which many negative impacts on ecosystems and humans . The many negative effects of pesticides would require alternative more environmentally friendly control . One alternative that can be recommended is the use of rhizobacteria which acts as a biological agent . The results showed that there were some rhizobacteria that effectively inhibit the growth of S. rolfsii Sacc . the inhibition test in vitro with the highest inhibition in the treatment of K. pneumoniae isolates KCX1GRA by 94.9 % when compared with controls at 3 days after inoculation observation . Rhizobacteria filtrate tested in vitro showed that the treatment of the filtrate concentration of 10 % - 20 % on respectively filtrate rhizobacteria able to inhibit the growth of fungus S. rolfsii Sacc . Treatment of the filtrate rhizobacteria isolates 20M2 and KCX1GRA concentration of 20 % -50 % able to kill the fungi S. rolfsii Sacc ., while the filtrate rhizobacteria isolates KCBS and Pi1 concentration of 30 % -50 % are also able to kill the fung i S. rolfsii Sacc . In the glass house study , the treatment was able to suppress rhizobacteria disease incidance in peanuts from 92 % to 8 % -10 % compared with the control treatment was 92 % at 6 weeks after planting observation . Keywords : rhizobacteria , biological agents , and S . rolfsii Sacc .